Association between statin use and outcomes in patients with coronavirus disease 2019 (COVID-19): a nationwide cohort study. Issue 12 (4th December 2020) - Butt, Jawad Haider; Gerds, Thomas Alexander; Schou, Morten; Kragholm, Kristian; Phelps, Matthew; Havers-Borgersen, Eva; Yafasova, Adelina; Gislason, Gunnar Hilmar; Torp-Pedersen, Christian; Køber, Lars; Fosbøl, Emil Loldrup
Abstract : Objective: To investigate the association between recent statin exposure and risk of severe COVID-19 infection and all-cause mortality in patients with COVID-19 in Denmark. Design and setting: Observational cohort study using data from Danish nationwide registries. Participants: Patients diagnosed with COVID-19 from 22 February 2020 to 17 May 2020 were followed from date of diagnosis until outcome of interest, death or 17 May 2020. Interventions: Use of statins, defined as a redeemed drug prescription in the 6 months prior to COVID-19 diagnosis. Primary and secondary outcome measures: All-cause mortality, severe COVID-19 infection and the composite. Results: The study population comprised 4842 patients with COVID-19 (median age 54 years (25th–75th percentile, 40–72), 47.1% men), of whom 843 (17.4%) redeemed a prescription of statins. Patients with statin exposure were more often men and had a greater prevalence of comorbidities. The median follow-up was 44 days. After adjustment for age, sex, ethnicity, socioeconomic status and comorbidities, statin exposure was not associated with a significantly different risk of mortality (HR 0.96 (95% CI 0.78 to 1.18); 30-day standardised absolute risk (SAR), 9.8% (8.7% to 11.0%) vs 9.5% (8.2% to 10.8%); SAR difference, −0.4% (−1.9% to 1.2%)), severe COVID-19 infection (HR 1.16 (95% CI 0.95 to 1.41); 30-day SAR, 13.0% (11.8% to 14.2%) vs 14.9% (12.8% to 17.1%); SAR difference, 1.9% (−0.7% to 4.5%)), and the composite outcome of all-cause mortality or severe COVID-19 infection (HR 1.05 (95% CI 0.89 to 1.23); 30-day SAR, 17.6% (16.4% to 18.8%) vs 18.2% (16.4% to 20.1%); SAR difference, 0.6% (−1.6% to 2.9%)). The results were consistent across subgroups of age, sex and presumed indication for statin therapy. Among patients with statin exposure, there was no difference between statin drug or treatment intensity with respect to outcomes. Conclusions: Recent statin exposure in patients with COVID-19 infection was not associated with an increased or decreased risk of all-cause mortality or severe infection.